Ratio of procalcitonin/Simpson’s dominance index predicted the short-term prognosis of patients with severe bacterial pneumonia - Sun, Guoxian; Liu, Weili; Zheng, Qingbin; Shan, Qing; Hou, Hongling (Frontiers in Cellular and Infection Microbiology, 2023)
Objective The aim of this study was to explore the predictive value of the ratio of procalcitonin (PCT) in serum to Simpson’s dominance index (SDI) in bronchoalveolar lavage fluid (BALF), in short-term prognosis of patients with severe bacterial pneumonia (SBP). Methods This is a retrospective review of case materials of 110 patients with SBP who selected BALF metagenomic next-generation sequencing technique in the intensive care unit (ICU) of the Affiliated Hospital of Yangzhou University from January 2019 and July 2022. Based on the acute physiology and chronic health status score II, within 24 h after admission to the ICU, patients were divided into a non-critical group (n = 40) and a critical group (n = 70). Taking death caused by bacterial pneumonia as the endpoint event, the 28-day prognosis was recorded, and the patients were divided into a survival group (n = 76) and a death group (n = 34). The SDI, PCT, C-reactive protein (CRP), PCT/SDI, and CRP/SDI were compared and analyzed. Results Compared with the non-critical group, the critical group had a higher PCT level, a greater PCT/SDI ratio, a longer ventilator-assisted ventilation time (VAVT), and more deaths in 28 days. Compared with the survivors, the death group had a higher PCT level, a lower SDI level, and a greater PCT/SDI ratio. The SDI level was significantly negatively correlated with the VAVT (r = −0.675, p < 0.05), while the PCT level, ratio of PCT/SDI, and ratio of CRP/SDI were remarkably positively correlated with VAVT (r = 0.669, 0.749, and 0.718, respectively, p < 0.05). The receiver operating characteristic (ROC) curves analysis showed that the area under ROC curves of PCT/SDI predicting patient death within 28 days was 0.851, followed by PCT + SDI, PCT, SDI, and CRP/SDI (0.845, 0.811, 0.778, and 0.720, respectively). The sensitivity and specificity of PCT/SDI for predicting death were 94.1% and 65.8%, respectively, at the optimal value (11.56). Cox regression analysis displayed that PCT/SDI (HR = 1.562; 95% CI: 1.271 to 1.920; p = 0.039) and PCT (HR = 1.148; 95% CI: 1.105 to 1.314; p = 0.015) were independent predictors of death in patients. Conclusion The ratio of PCT/SDI was a more valuable marker in predicting the 28-day prognosis in patients with SBP.